Distinguishing lard from other animal fats in admixtures of some vegetable oils using liquid chromatographic data coupled with multivariate data analysis - Marikkar, Mohammed Nazrim; Ghazali, H.M.; Che Man, Y.B.; Peiris, T.S.G.; Lai, O.M. (Elsevier, 2005)
Detection of animal fat adulterants in vegetable oils is of great importance from the commercial and health perspectives. Distinguishable identification of lard contamination in some vegetable oils has been attempted in this study. Vegetable oils namely palm oil (PO), palm kernel oil (PKO), and canola oil (CLO) were spiked with different proportions of animal fats such as lard (GLD), beef tallow (BT), and chicken fat (CF). High performance liquid chromatographic (HPLC) analyses were performed to monitor the triacylglycerol (TAG) compositional changes in the oil samples before and after adulteration. The results showed that qualitative determination of lard contamination in PKO was possible by a visual comparison of TAG profiles of PKO adulterated with different animal fats with those of the animal fats whereas this approach could not be found useful for PO and CLO. However, by subjecting liquid chromatographic data into multivariate procedures, distinguishable grouping for lard-contaminated samples was achieved for all the three oils.